Hermeneutic Understanding of Reason & Religion in the Context of Islam Revitalization discourse - Abbasali Rahbar (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2013)
Hermeneutic understanding of the problem and understanding the dilemma of modern hermeneutics, and it responds with an understanding of the interaction between action and language. With emphasis on the developments made in the realm of politics, reason and religion from the perspective of hermeneutic understanding human cognitive processes is very important. Bearing in mind that this is a significant component in any sense of reason and religion are different epistemological and can only be used as a quick method to help them understand. This article looking for this hypothesis that being update with Contemporary conceptions of reason and religion, reason and faith between the old perception of change will occur with time and space requirements in understanding the reason religion helps. Sunni scholars to understand the new law and understand the intentions of the continuity theory of jihad in understanding Sharia scholars are Shia. Based on a view of discourse, dialogue with the understanding of the Islamic resurgence of religion as a social issue and multidimensional focus on the dignity of man, and divine traditions with renewed attention to rationality derived from revelation